Marital status and age of systemic lupus erythematous diagnosis: the potential for differences related to sex and gender - Évelyne Vinet; Sasha Bernatsky; Eugene Brailovski; Christian A Pineau; Jennifer Lee; Luck Lukusa; Fares Kalache; Louis-Pierre Grenier; Deborah DaCosta (Lupus Science and Medicine)
Objectives Chronic rheumatic diseases can challenge social and family relationships. We compared marital status in patients with systemic lupus erythematous (SLE) with their general population counterparts, stratified by sex and age of SLE onset.Methods We performed a cross-sectional analysis of a cohort of 382 patients with SLE at our centre (349 females, 33 males). We determined how many were married or living common-law at the time of last study visit. Patients were then divided into: SLE diagnosis before 18, between 18 and 30, between 31 and 44 and after 45 years of age. We then compared marital status among male and female patients with SLE, to Quebec age-specific marital statistics.Results Of 382 patients with SLE, 202 (52.9%) were married or living common-law, which was 9% lower than general population rates (95% CI 2% to 16%). One-third of women with paediatric-onset SLE were married or living common-law, which was 28% lower than their general population counterparts (95% CI 6% to 46%). Half of women diagnosed between age 18 and 30 were married or living common law, which was 14% less than general population rates (95% CI 4% to 25%). We could not establish significant differences for women diagnosed after age 30, or for males, versus their general population counterparts.Conclusions Women diagnosed with SLE before age 30 were less likely to be married/living common-law, versus general population rates. This was not apparent for those diagnosed later in life. We did not clearly establish this effect in males, possibly due to power issues (vs a true effect of sex/gender). Additional studies (eg, focus groups) could elucidate reasons for our findings.